Proměny a konstanty Helfertova psaní o Janáčkovi - Miloš Zapletal (Musicologica Brunensia, 2016)
The study deals with development of Vladimír Helfert's writing about Leoš Janáček from the period 1911–1939 and presents the results of a discourse analysis of Helfert's texts (both musical-critical and historiographical) on Janáček. In his texts, Helfert ignored Janáček until the beginning of the First World War: this was the time of "struggle against Dvořák", in which Helfert stood on Zdeněk Nejedlý's side. Helfert wrote his first text on Janáček in 1915, but it was not until he moved to Brno in the summer of 1919 that he began to regard Janáček favourably. The turnover in his writing on Janáček occurred in 1920, when Helfert transformed some former conceptual negatives into positives. After Janáčekian anniversary festival in 1924, Helfert started to write about Janáček more frequently and systematically, and, around 1925, a coherent critical conception of Janáček started to emerge from his writing. In many aspects, it was similar to Nejedlý's conception of the Great Czech Composer. In the following years, Helfert further developed this conception and gradually recognized Janáček as a  classical figure of modern Czech music; this process culminated in the first part of his unfinished monograph on Janáček from 1939. The basic features of his conception are the following: (1) organicity of Janáček's artistic development and inclusion of Janáček into the organicist model of the evolution of modern Czech music; (2) contraposition of Janáček and other great Czech composers, and the view of Janáček as a sheer individuality; (3) recognition of some negatives of Janáček's musical thought as positives in their own rightspecific qualities ("elementariness", non-constructiveness, aphoristicity, etc.); (4) Janáček as a completely new, revolutionary type of composer; (5) identity of the character of the composer's personality and the character of his music; (6) Janáček as a primarily vocal and dramatic composer; (7) Janáček as a Beethovenian genius; (8) the myth of eternally young Janáček; (9) Janáček as an essential realist and, therefore, anti-romantic; and (10) emphasising Janáček's Russianisms or Slavicness.